Dakwah Media Sosial: Alternatif Dakwah Kontemporer - Faldiansyah, Iqrom; Musa, Musa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
Dakwah Social Media is a must that must be thought of and implemented by dakwah actors. Social media preaching has many advantages including being able to penetrate space and time boundaries with relatively affordable costs and energy. Communicating da'wah as a large area of land because users of internet services have increased dramatically every year. Social media preaching has become a variant of public choice. They are free to choose the da'wah material they like. Thus, da'wah is more egalitarian and far from being coercive. Varied delivery methods make social media preaching able to reach a wider range of mad'u. The da'wah movement must pay attention to various accompanying problems that arise in society. As a consequence, a da'i or mubaligh must be part of the whole society who aspires to build a civilized and prosperous life. Because of that, what he should